2021
DOI: 10.1101/2021.01.29.21250762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Prognosis in COVID-19 Patients using Machine Learning and Readily Available Clinical Data

Abstract: RationalePrognostic tools for aiding in the treatment of hospitalized COVID-19 patients could help improve outcome by identifying patients at higher or lower risk of severe disease.ObjectivesThe study objective was to develop models to stratify patients by risk of severe outcomes during COVID-19 hospitalization using readily available information at hospital admission.MethodsHierarchical ensemble classification models were trained on a set of 229 patients hospitalized with COVID-19 to predict severe outcomes, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Campbell et al [33] devised hierarchical ensemble classification models for the prediction of several severe events connected with Covid-19 based on laboratory and clinical data available at admission. Due to missing values they removed about 50 percent of the training data and 85 percent of test data.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell et al [33] devised hierarchical ensemble classification models for the prediction of several severe events connected with Covid-19 based on laboratory and clinical data available at admission. Due to missing values they removed about 50 percent of the training data and 85 percent of test data.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have employed diverse predictive indicators in their investigation of COVID-19 to evaluate the prognosis of the disease's ultimate clinical outcome. These predictive indicators comprise blood samples, electrocardiograms, imaging data (CT, XCR), respiratory parameters, clinical symptoms, and other relevant information [28][29][30][31][32][33][34][35] . The concluding indicators of the study were also varied, with a primary focus on the severity of the illness, the risk of mortality, the actual mortality rate, the length of hospitalization, and other relevant factors.…”
Section: The Implementation Of Ai In Forecasting the Medical Conditio...mentioning
confidence: 99%
“…Campbel et al (2021) [23] develop predictive models that stratify hospitalised COVID-19 patients by their risk of severe outcomes, such as ICU admission, acute respiratory distress syndrome development, or intubation. The models were designed using hierarchical ensemble classification techniques and trained on a dataset of 229 COVID-19 patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, attributes such as C-reactive protein, lactate dehydrogenase, and D-dimer were frequently identified as significant contributors to the risk assessments. The study concluded that machine learning-based models utilising routinely collected admission data can effectively assess the risk of severe outcomes in COVID-19 patients during hospitalisation [23].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation